The effect of reading activities in the development of critical thinking in 10th grade students from Virgen del Cisne School. - Velez Parrales, Ambar Valeria (2023)
Various perspectives regarding the impact of reading activities on the enhancement of critical thinking skills are examined, emphasizing their significance in the realm of education. The initial section delves into philosophical and psychological viewpoints on critical thinking and their role in shaping educational practices. Hence, this research endeavor was undertaken to explore the impact of reading comprehension activities on the advancement of critical thinking. Additionally, it aimed to investigate teaching methods and strategies that could enhance the learning experience. The study also sought to gain insights through interviews with students from Virgen del Cisne. This research undertaking utilized a qualitative methodology, focusing on a specific case study named "THE EFFECT OF READING ACTIVITIES IN THE DEVELOPMENT OF CRITICAL THINKING IN 10TH GRADE STUDENTS FROM VIRGEN DEL CISNE SCHOOL." The study involved gathering data from primary sources, including interviews with students, as well as secondary sources such as literature reviews of journals, books, and papers. Interviews were carried out with eight students from Virgen del Cisne School. The study sample revealed diverse viewpoints regarding the enhancement of critical thinking skills through these reading activities. Based on the gathered information and the examination of previous studies, it can be inferred that placing greater emphasis on reading comprehension activities is essential for fostering the growth of critical thinking. Furthermore, these findings can serve as a foundation for future research to conduct more comprehensive analyses from different perspectives.